The essential role of YAP in ERα36-mediated proliferation and the epithelial-mesenchymal transition in MCF-7 breast cancer cells - Park, Miso; Lee, Seung Hyun; Bui, Quyen Thu; Kim, Young-Mi; Kang, Keon Wook (Frontiers in Pharmacology, 2022)
Purpose: Most breast cancers are hormone-receptor-positive, and thus the first-line therapy for them is an anti-estrogen medication such as tamoxifen. If metastasis occurs or resistance to tamoxifen develops, the 5-year survival rates for breast cancer patients significantly decrease. Hence, a better understanding of the molecular mechanisms that contribute to breast cancer aggressiveness is of great importance. ERα36 is an estrogen receptor variant that is known to be upregulated in breast cancer patients receiving tamoxifen treatment or in triple-negative breast cancer cells. However, the specific molecular mechanism underlying ERα36-induced tamoxifen-resistance is not yet fully understood. Methods: ERα36-overexpressing MCF-7 cells were constructed by either plasmid transfection using ERα36 vector or retroviral infection using ERα36-V5-His vector. Target-gene expression was assessed by Western blot analysis and real-time PCR, and YAP activation was evaluated by luciferase assays and immunofluorescence. Cell proliferation and formation of three-dimensional spheroids were evaluated using the IncuCyte S3 Live Cell Analysis System. Results: We found that the expression patterns of Hippo signaling-related genes were significantly changed in ERα36-overexpressing MCF-7 cells compared to MCF-7 cells, which were also similarly observed in tamoxifen-resistant MCF-7 cells. Specifically, the protein expression level and activity of YAP, the core downstream protein of the Hippo pathway, were significantly increased in ERα36-overexpressing MCF-7 cells compared with MCF-7 cells. The aggressive phenotypes acquired by ERα36 overexpression in MCF-7 cells were destroyed by YAP knockout. On this basis, we propose that ERα36 regulates YAP activity by a new mechanism involving Src kinase. Conclusion: Our results suggest that YAP targeting may be a new therapeutic approach to the treatment of advanced breast cancers overexpressing ERα36.